Acidithiobacillus Thiooxidans Secretome Containing a Newly Described Lipoprotein Licanantase Enhances Chalcopyrite Bioleaching Rate - Levican-Jaque, G (2011)
The nature of the mineral-bacteria interphase where electron and mass transfer processes occur is a key element of the bioleaching processes of sulfide minerals. This interphase is composed of proteins, metabolites, and other compounds embedded in extracellular polymeric substances mainly consisting of sugars and lipids (Gehrke et al., Appl Environ Microbiol 64(7):2743-2747, 1998). On this respect, despite Acidithiobacilli-a ubiquitous bacterial genera in bioleaching processes (Rawlings, Microb Cell Fact 4(1):13, 2005)-has long been recognized as secreting bacteria (Jones and Starkey, J Bacteriol 82:788-789, 1961; Schaeffer and Umbreit, J Bacteriol 85:492-493, 1963), few studies have been carried out in order to clarify the nature and the role of the secreted protein component: the secretome. This work characterizes for the first time the sulfur (meta)secretome of Acidithiobacillus thiooxidans strain DSM 17318 in pure and mixed cultures with Acidithiobacillus ferrooxidans DSM 16786, identifying the major component of these secreted fractions as a single lipoprotein named here as Licanantase. Bioleaching assays with the addition of Licanantase-enriched concentrated secretome fractions show that this newly found lipoprotein as an active protein additive exerts an increasing effect on chalcopyrite bioleaching rate. © 2010 The Author(s).